2009
DOI: 10.1007/s00167-008-0709-5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the femoral origin and tibial insertion morphology of the ACL

Abstract: Transtibial single bundle anterior cruciate ligament (ACL) reconstruction has been the gold standard for several years. This technique often fails to restore native ACL femoral origin and tibial insertion anatomy of the ACL. Recently, there is a strong trend towards a more anatomical approach in single and double bundle ACL reconstruction. Using the anatomic double bundle structure of the ACL as a principle, the entirety of both tibial insertion and femoral origin of both bundles, the posterolateral and antero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
201
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 250 publications
(217 citation statements)
references
References 50 publications
7
201
0
7
Order By: Relevance
“…Concerns about the optimal position for ACL reconstruction have sparked extensive study into the shape, orientation, and attachment points of the native ligament, especially regarding the femoral attachment. 7,8,10,15,24,28,32 The femoral soft tissue attachment of the ACL is not a circle but an ellipse, as recently highlighted by Fu and Jordan,9 who noted along with others that the majority of the fibers lie posterior and proximal to the lateral intercondylar ridge. More recently, Iwahashi et al 14 demonstrated a direct and indirect insertion of the ACL on the femoral condyle, with the direct insertion of the ligament acting as ''a key link between the ligament and bone to transmit mechanical load to the joint.''…”
mentioning
confidence: 90%
“…Concerns about the optimal position for ACL reconstruction have sparked extensive study into the shape, orientation, and attachment points of the native ligament, especially regarding the femoral attachment. 7,8,10,15,24,28,32 The femoral soft tissue attachment of the ACL is not a circle but an ellipse, as recently highlighted by Fu and Jordan,9 who noted along with others that the majority of the fibers lie posterior and proximal to the lateral intercondylar ridge. More recently, Iwahashi et al 14 demonstrated a direct and indirect insertion of the ACL on the femoral condyle, with the direct insertion of the ligament acting as ''a key link between the ligament and bone to transmit mechanical load to the joint.''…”
mentioning
confidence: 90%
“…29 In the literature, there is a high degree of intrastudy and interstudy variation in the sizes of the femoral and tibial ACL insertions. 49 In general, the size of the femoral insertion is slightly smaller and of a different shape than the tibial insertion, which needs to be considered when performing anatomic ACL reconstruction.…”
Section: Anatomy Of the Aclmentioning
confidence: 99%
“…Therefore, even though the ACL is located intra-articularly, it is developmentally an extrasynovial structure. Macroscopically, the mature ACL originates from the medial aspect of the lateral femoral condyle in the intercondylar notch and inserts into the interspinous area of the tibia [12]. The ACL is composed of the anteromedial bundle (AMB), which is tight in flexion and limits the anterior translation of the tibia in relation to the femur.…”
Section: Anatomymentioning
confidence: 99%